POSSIBLE IMPACT OF THE ABE-KURO MONETARY EXPANSION ON THE INDONESIAN ECONOMY - Abimanyu, Yoopi (Badan kebijakan Fiskal, 2013)
Abenomics, the economic policies of Japan, which recently has been changed into